An analysis of scenography functions: Visual communication through the SARAH theatre [Analisis fungsi sinografi: Komunikasi visual melalui pementasan teater SARAH] - Mohd Amir Mohd Zahari (Tanjung Malim, 2023)
An analysis of scenography functions: Visual communication through the SARAH theatre [Analisis fungsi sinografi: Komunikasi visual melalui pementasan teater SARAH] by Mohd Amir Mohd Zahari